The Role and Development of Supplementary Reading Materials in EFL Teaching - Ngabalin, Inaya (Huele: Journal of Applied Linguistics, Literature and Culture, 2023)
This library research examines the theoretical foundations and practical implications of developing supplementary reading materials for English as a Foreign Language (EFL) teaching. Through comprehensive analysis of existing literature, this study investigates supplementary materials' characteristics, benefits, and implementation strategies in language classrooms. The findings reveal three key aspects of effective supplementary materials: their essential characteristics, including complementary function and learner-centered design; their benefits, particularly in promoting learner autonomy and motivation; and crucial considerations for their development and implementation. Research indicates that well-designed supplementary materials significantly enhance student engagement, facilitate independent learning, and improve overall language proficiency. The study demonstrates that successful supplementary materials maintain clear connections to core curriculum objectives while offering flexibility in application and implementation. Analysis of classroom implementations reveals that materials incorporating varied learning modalities and providing clear progression paths produce more consistent learning outcomes. This research contributes to the understanding of supplementary material development in language teaching and provides practical insights for material developers and educators in the EFL context. The findings emphasize the importance of systematic development approaches that consider both pedagogical principles and practical implementation concerns, suggesting the need for continued research into effective development and implementation strategies.